Evaluación de erradicacion del cocotero para el manejo del anillo rojo Bursaphelenchus cocophilus – gualpa Rhynchophorus palmarum (Coleoptera: curculionidae) en Tumaco - Nariño - Grueso H., Washington; Betancourth, Carlos (Revista de Ciencias Agrícolas, 2009)
This study was realized in two zones of Tumaco's Municipality, that includes Chagüi and Mejicano rivers. The objetive was to evaluate the technique of coconut palm eradication to the management of the Red Ring nematode Bursaphelenchus cocophilus - Gualpa Rhynchophorus palmarum (CARG) complex. Inside every zone 30 farms were selected and divided in two groups: 3 hectares lowers and others to 3 up to 10 hectares highers. the initial incidence level was determined to the zones 1 and 2, which was 37.91 % and 37.99% respectively. Then the affected palms were eliminated periodically to the first, third and sixth month. For it mechanical saws were used and the palms were cut in four pieces to extract the insect's larvaes and pupaes. Finally between zones 1 and 2 a total quantity of 15.984 palms were eradicated, where were found 28.173 larvaes and 4.687 pupaes. As complementary strategy, the population of insect adults R. palmarum diminished using traps provided with baits and pheromones. The register of females and males was of 17.485, respectively was found that the population of R. palmarum has a directly proportional relationship with the disease incidence, since the higher population, the higher CARG incidence; which with adequate and constant trapping and elimination of the affected palms can diminish its incidence.